2010
DOI: 10.1186/ar2972
|View full text |Cite
|
Sign up to set email alerts
|

Olf1/EBF associated zinc finger protein interfered with antinuclear antibody production in patients with systemic lupus erythematosus

Abstract: IntroductionThe aim of the study was to determine whether Olf1/EBF associated zinc finger protein (OAZ), a transcription factor encoded by a positional systemic lupus erythematosus (SLE) candidate gene, plays a functional role in the pathogenesis in SLE.MethodsGene expression levels in peripheral blood cells (PBLs) measured using quantitative real-time polymerase chain reaction (qPCR) were assessed for association with disease activity and the presence of specific autoantibodies. Peripheral blood mononuclear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 48 publications
2
12
0
Order By: Relevance
“…Consistent with ours [11], several studies have also provided evidences that the IL-21 pathway plays an important role in the pathogenesis of SLE [18], [19]. The production of IL-21 is mainly restricted to two subsets of CD4 + T cells, Th17 and Tfh.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with ours [11], several studies have also provided evidences that the IL-21 pathway plays an important role in the pathogenesis of SLE [18], [19]. The production of IL-21 is mainly restricted to two subsets of CD4 + T cells, Th17 and Tfh.…”
Section: Discussionsupporting
confidence: 87%
“…Previously we have shown there was a nearly perfect correlation between the extent of IL-21 and ANA production in vitro [11], strongly supporting a role of Tfh cell in the developing of SLE. However, it is still unclear how these cells are modulated in SLE.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Accell small interfering RNAs (siRNAs) targeting SMG7 (E-021305), glyceraldehyde 3-phosphate dehydrogenase ( GAPDH , as positive control; D-001930) or with non-targeting sequences (as negative control; D-001910) were synthesised by Dharmacon 12. PBMCs from 13 patients with SLE were isolated by Ficoll-Hypaque, resuspended in Accell delivery media plus 3 μM siRNA, distributed to 96-well plates at 2×10 5 cells/well, and divided into silence groups for SMG7 , GAPDH , non-targeting and medium-only mock controls.…”
Section: Methodsmentioning
confidence: 99%
“…The underlying causes of diffuse B cell overreactivity in this disease are still unclear. We previously showed that a lupus candidate gene named olfactory 1/early B cell factor–associated zinc‐finger protein (OAZ), identified within the 16q interval in a Chinese cohort (), was highly expressed in patients with SLE and was associated with autoantibody production (). The suppression of OAZ expression in peripheral blood mononuclear cells (PBMCs) from patients with SLE could directly inhibit ANA secretion and reduce total IgG levels, supporting a role of OAZ in the regulation of B cell function ().…”
mentioning
confidence: 99%